Preventive Interfaith Marriage Conflicts Through Assistance for Hindu Families Based on Swadharma Grahasta Dormitory in Ngis Hamlet, Buwun Sejati Village, Narmada District, West Lombok Regency - I Ketut Putu Suardana; Sayu Kadek Jelantik; Rieka Yulita Widaswara; Ni Nyoman Harnika (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
The community service program carried out by the Hindu Religious Information Study Program aims to strengthen religious character, increase sradha and devotion to the younger generation of Hindus through family communication based on swadharma grahasta asrama to improve the method used, namely service learning which consists of the preparation stage, service stage, and also the reflection stage. The results of this service are that there is a strengthening of religious character in the form of increasing devotional service for the younger generation of Hindus through family communication assistance, the formation of the Widya Gitanjali Pasraman as a non-formal educational institution as a forum for learning Hinduism for the younger generation of Hindu Dusun Ngis in an effort to strengthen character, increase sradha and bhakti in an integrated manner, sustainable